Legal Consequences for Auction Winners who Commit Contingency in Auction of Dependents - Moh. Faizin; Zhelin Armeta; Adil Sembiring (Universitas Muhammadiyah Palu, 2025)
This study analyzes the legal consequences for auction winners involved in the auction of dependent rights due to the implementation of the execution of the right of dependency auction in Indonesia which often does not follow standard procedures, such as unreasonable limit pricing, lack of notification to debtors, and indications of collusion between creditors, auction officials, and auction winners. The method used in this study is normative juridical with a legislative approach, a case approach, and a conceptual approach. The results of the study show that the panel of judges in the case declared the auction process invalid because it was proven to violate the principles of transparency, accountability, and fairness in the implementation of state auctions. The auction winner is declared not entitled to acquire the auction object due to his involvement in a legally defective process, thus losing the legal protection that should be given to the auction winner in good faith. A judgment ordering the return of the auction object to the debtor is also a form of restoration of substantive justice. Analysis of the verdict using John Rawls' theory of justice shows that the verdict is in line with the principle of justice as fairness, especially in the protection of the most disadvantaged parties and correction of unfair procedures.